Consolidação do Primeiro Comando da Capital (PCC) no sistema carcerário paulista e a nova configuração do poder - Camila Nunes Dias (L'Ordinaire des Amériques)
Over the past two decades, the physical situation of prisons has worsened due to the dramatic growth of the prison population. In the wake of this process, a group of prisoners, naming itself the First Command of the Capital (FCC), came into being. Throughout this period, its capacity for structuring and articulating reached an unprecedented level. The consolidation of the FCC within the prison system, its transformation into a conflict-regulating body and at the same time into a provider of basic goods and services for some prisoners and their families, have resulted into a reshaping of power in prisons. The various forms of expression of its power and modes of action suggest that the history of FCC expansion is divided into three phases. Between 1993 and 2001: formation and conquest of territories; between 2001 and 2006: consolidation and public recognition of its power; from 2006 on: hegemony. Those three phases testify to the changes that have occurred within and without the FCC, in its forms of organization and action, creating a specific social process, of an economic as well as a political kind, the most visible effect of which is the so designated "pacification" of the territories it controls.